EFFECT OF EPIDURAL ANALGESIA ON LABOR AND ITS OUTCOMES - Anwar, Sadia; Anwar, Muhammad Waseem; Ayaz, Attiya; Danish, Nargis; Ahmad, Sajjad (Journal of Ayub Medical College Abbottabad, 2015)
Background: Epidural analgesia is an effective and popular way to relieve labour pain but it may interfere with normal mechanism of labour. The objective of this study was to evaluate the outcome of labour in women with effective epidural analgesia in terms of duration of labour, mode of delivery and neonatal outcome. Methods: This was a quasi-experimental study conducted in the Department of Obstetrics and Gynaecology, Shaikh Zayed Federal Postgraduate Medical Institute and Hospital, Lahore. One hundred pregnant women were selected by non-probability convenient sampling method. Subjects were divided into two groups of 50 each as per convenience. Patients of any gravidity at term from 37-41 weeks were included in the sample. Epidural analgesia was applied to group B and distilled water to group A at the lumber region and the progress of labour, mode of delivery and effects on Apgar scores of neonates were evaluated. Out of hundred patients, 77 had normal duration of second stage while 23 had prolonged second stage. Among them, 18 patients (36%) were in epidural group and 5 patients (10%) in non-epidural group, while 4 patients (8%) in epidural group developed intra-partum complications; whereas among non-epidural group had such complications. 65 patients had spontaneous vaginal delivery while 35 patients had instrumental delivery. Among them 29 patients (58%) were in epidural group while only 6 patients (12%) were in non-epidural group. Babies born had Apgar score 5/10 (21.8%), 6/10 (59.4%) and 7/10 (17.8%) at 1 minute and 8/10 (74.3%) and 9/10 (24.8%) at 5 minutes in both groups and none of them needed bag and mask resuscitation. Conclusion: Epidural analgesia does prolong the duration of second stage of labour and increases the instrumental delivery rate. Neonatal outcome is satisfactory while only a few intra-partum complications are found with epidural analgesia. Keywords: Epidural analgesia, forceps, labour, parturition, Apgar score, Neonatal outcome